2006
DOI: 10.1002/anie.200602036
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Dielectric Properties of Pure‐Silica‐Zeolite Low‐k Materials

Abstract: Special k: Pure silica zeolites (PSZs) have been shown experimentally to display a remarkably higher elastic modulus than amorphous porous silicas at any given porosity or dielectric constant (k) value as a result of their crystalline structure. The combined experimental and theoretical findings suggest that PSZs have the necessary properties for use as the next generation of low‐k insulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 142 publications
(54 citation statements)
references
References 24 publications
2
51
0
1
Order By: Relevance
“…This porosity is also in agreement with results from the Maxwell Garnett model [33] applied to MFI with refractive index reported to be 1.39 [22] and a solid matrix with refractive index of quartz equal to 1.543 at 627.8 nm [34]. Finally, MEL thin film porosity measurements were also in good agreement with previous nitrogen adsorption measurements on powder samples [6,28].…”
Section: Comparison Between Psz Mel and Psz Mfi Filmssupporting
confidence: 80%
See 2 more Smart Citations
“…This porosity is also in agreement with results from the Maxwell Garnett model [33] applied to MFI with refractive index reported to be 1.39 [22] and a solid matrix with refractive index of quartz equal to 1.543 at 627.8 nm [34]. Finally, MEL thin film porosity measurements were also in good agreement with previous nitrogen adsorption measurements on powder samples [6,28].…”
Section: Comparison Between Psz Mel and Psz Mfi Filmssupporting
confidence: 80%
“…The present study establishes that the dielectric constant of MEL thin films can be reduced without decreasing the film's thermal conductivity. Furthermore, dielectric constant as low as 1.5 were reported for PSZ MEL thin films with porosity of 64% [28]. This is as low as that of sol-gel templated mesoporous silica thin films of similar porosity [41][42][43].…”
Section: Comparison Of Thermal and Dielectric Propertiesmentioning
confidence: 85%
See 1 more Smart Citation
“…Older studies by Astala et al 6 reported computed elastic properties of several frameworks including silicalite, whose comparison with experimental data was however controversial. Li et al 7 have investigated experimentally zeolite structures with low dielectric constant and measured elastic constants as a function of porosity.…”
Section: Methodsmentioning
confidence: 99%
“…Since silicon is tetravalent, pure-silica zeolites (PSZs) do not contain framework charges and consequently no cations, which would be detrimental for electronic applications, are present. Due to their dense crystalline structure, better mechanical properties are expected [131], and since their pore size (< 2 nm) is significantly smaller than integrated circuit (IC) features, the problem of electrical breakdown should be mitigated by the absence of any randomly occurring large pores.…”
Section: Silica Zeolitesmentioning
confidence: 99%